Harmonizing Pancasila and Islamic Moderation as a Digital Ethical Framework: A Grounded Strategy of Teacher-Community Synergy - Mukhamad Ainul Yaqin (Afkaruna: International Journal of Islamic Studies (AIJIS), 2026)
In the era of hyper-connectivity, the massive spread of disinformation and intolerance poses a significant threat to Indonesia’s national cohesion. This study explores how the national ideology, Pancasila, is operationalized into a practical framework for tolerance education by local actors in Lumbang, East Java—a region known for its distinct multicultural harmony. Employing a Grounded Theory approach with in-depth interviews, this research analyzes the synergistic strategies of two key agents: teachers and community leaders. The findings reveal that digital media in this region functions not to create, but to amplify existing social harmony. Teachers act as strategic communicators, applying Inoculation Theory by proactively "injecting" cognitive defenses against hoaxes and positioning Pancasila as a critical ethical filter in the classroom. Conversely, Community Leaders operate as gatekeepers who prioritize "heart-to-heart" interpersonal communication over digital interactions to mitigate conflicts, viewing social media as a supplementary tool rather than a primary solution. The study concludes that Pancasila is successfully revitalized not as a mere abstract concept, but as a "lived digital ethics" or shared frame of reference. This research offers a unique bottom-up model of digital resilience where formal pedagogical structure and informal communal wisdom intersect to sustain tolerance.